The english club as a non formal space for university-local context articulation - Mendoza Bravo, Karina Luzdelia; Castellanos Noda, Ana Victoria (Atenas, 2017)
In this research is presented a proposal for a scientific solution to the short comings identified in the teaching-learning of the English language in high school, Portoviejo city, Ecuador, based on critical reflection of the current educational context and teaching and research experiences of one of the authors. The project to carried out through the English club, as a non-formal teaching and learning place, assumed to be direct beneficiaries both, high school students and college students, as far as possible to enhance the development of oral production in the first, while promoting positive changes in teacher training of the seconds.